Weaving Textual Tapestries: The Role of the Biblical Intertext - Vorchheimer, Hannah (Iggrot Ha’Ari, 2022)
In Medieval Iberia, Arabic was perceived as the most communicative, practical, and beautiful language. Forced to contend with this, authors of Hebrew works sought to raise the caliber of the Hebrew language. This paper will explore the use of these Biblical intertexts through an intertextual analysis of Judah Halevi’s poem “Song of Farewell.” These intertexts utilized the contexts of their original stories to convey a deeper meaning to the literary works as well as create additional layered meaning subsequently aiding in the reinvigoration of the Hebrew language.